Perceptions on renewable energy use in Malaysia: mediating role of attitude - Azhar Ahmad; Mamunur Rashid; Nor Asiah Omar; Syed Shah Alam (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study investigates the perception towards renewable energy use in Malaysia. A survey of in the Klang-valley area yield responses from 200 respondents. Then, the data were analysed using exploratory factor analysis and multiple regression analysis. Five factors emerge from the factor analysis namely relative advantage, perceived behavioural control, ease of use, awareness, and benefit-cost trade-off. Multiple regression analysis is conducted to examine the explanatory power of these five factors in predicting the intention to use renewable energy. Results of the analysis show that 1) relative advantage and perceived behavioural controls positively mediate attitude towards renewable energy and 2) attitude positively mediates intention to use renewable energy. However, ease of use, benefit-cost trade-off and awareness positively but directly influence intention to use renewable energy. In conclusion, this study contributes to the literatures on social barriers to renewable energy in emerging nations and on theory of planned behaviour.